The Fiscal Effects of Monetary Policy - Dahan, Momi. (Washington, D.C. : International Monetary Fund, 1998)
This paper develops a simple framework to examine the budgetary implications of monetary policy measures. It further outlines, using this framework, the various channels of influence that tight monetary policy may have on the budget deficit. The cumulative effect might be quantitatively large although each effect might be small. Most of the effects tend to increase the budget deficit as result of tight monetary policy, but tight monetary policy causes a short-run decrease in the government debt. Thus, macroeconomic policy coordination should be considered.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet